Academic Procrastination and Self-Control in Thesis Writing Students of Faculty of Psychology, Universitas Surabaya - Ursia, Nela Regar; Siaputra, Ide Bagis; Sutanto, Nadia (UI Scholars Hub, 2013)
Procrastination has long been regarded as reflection of low self-control. The emergence of temporal motivation theory (TMT) as a theoretical framework to explain procrastination also supports the role of self-control in bringing forth procrastination. This study aimed to test the suitability of TMT in explaining correlational pattern of self-control and procrastination, both in general and in thesis completion. Subjects were 157 psychology students working on their thesis. The results show that self-control has a negative correlation with general procrastination (r = -0.663) and thesis (r=-0.504). The role of TMT’s elements as mediators has been proven when the negative correlations weakened significantly after controlling for TMT elements. Nevertheless, a greater attenuation was actually found when self-control was used as the mediator variable. Alleged causes and implications of the findings are discussed. Keywords: general procrastination, self-control, temporal motivation theory, undergraduate thesis procrastination Keywords: